A arquitetura, o corpo e o espelho sobre a beleza e o tempo na arte do Renascimento e em nossos dias - D'Agostino, Mário Henrique Simão (Tempo Social, 2003)
The revival of the old ideal of "eternal fame" and "perpetuity" in art allows for a new conceptual framing of the classical principle of mimesis, in the Renaissance. Asserting the preeminence of Architecture over all the other arts, various renaissance papers link the making of beautiful works to the longevity of the buildings (Chrysolaras, Alberti, Filarete, Cesariano, among others). The curatorship and the exemplary value of the monuments, coordinated to the norm of imitating the antichi, bring about different doctrinarian positions on the meaning of time in art to regulate classicisms up to the 18th century. On the other hand, by looking back on the challenges issued then allows one to make a more removed and critical appraisal on the diffuse "cult" of time and beauty, currently in fashion.